Antioxidant, Antimicrobial, Anti-Inflammatory, and Gut Microbiota Modulation Effects of Kombucha: a Literature Review - Hananta, Linawati; Kurniawan, Sandy Vitria; Lonah; Arieselia, Zita; Surjono, Edward; Setiawan, Jonny; Lieputra, Andrew Adhytia; Puspa Bunardi, Dewi; Prayoga Tjendratama, Jason; Vallerie Satyadi, Richelle; Dewi, Rita (Journal of Urban Health Research, 2025)
Introduction: The interest in probiotics has increased significantly in recent years. While most probiotic-containing foods are dairy-based, an increasing number of non-dairy probiotic products have emerged, including kombucha. Kombucha is a fermented tea beverage originating from China, known for its high polyphenol content and potential health benefits. Methods: This literature review aims to provide a comprehensive understanding of the health benefits of kombucha. A systematic search of published studies was conducted using the keywords "kombucha," "antioxidant," "anti-inflammatory," "antimicrobial," and "gut microbiota modulation." Only English-language articles were included, and there was no restriction on publication date to capture the full spectrum of research on kombucha. Results: Kombucha exhibits significant antioxidant capacity, with green tea kombucha demonstrating the highest Ferric Ion Reducing Antioxidant Power (FRAP) due to its high polyphenol content. Additionally, kombucha possesses antimicrobial properties attributed to organic acids, lactones, aldehydes, fatty acids, and alkaloids, which act synergistically. It also exhibits anti-inflammatory effects by inhibiting nitric oxide production and downregulating pro-inflammatory cytokines such as IL-1β and TNF-α. Furthermore, kombucha modulates gut microbiota composition by inhibiting the growth of Gram-negative bacteria, leading to reduced systemic inflammation and oxidative stress. Conclusion: Kombucha, a traditional fermented tea, has notable health benefits, including antioxidant, antimicrobial, anti-inflammatory, and gut microbiota-modulating properties. These findings highlight its potential as a functional beverage for health promotion. Keywords: kombucha – antioxidant - anti-inflammatory – antimicrobial - gut microbiota modulation